Ephemeral Domesticity: Campsite - Capomaggi, Julia (Interiority, 2024)
The fleeting nature of life and the resulting transformation of inhabited spaces into artefacts that take on different socio-spatial forms through temporary shelters such as cabins, tents, and trailers is a major theme explored particularly in the 1960s and 1970s that introduced the concept of time into the formation of transient communities. This article focuses on the issue of the endless interior generated by transience in group living linked to tourism and recreational leisure, specifically elective nomadism, which represents alternative models of colonisation and the relationship between habitat and nature. Although the origins of these ideas can be traced back to projects and manifestos of experiments in utopian cities, some aspects of these avant-garde principles can be seen in communities linked to vacation, leisure, and free time today. Lastly, the campsites in Girona serve as an example and case study where these theoretical principles have been spontaneously implemented and are now subject to regulation. They have shaped a model where the city is internalised and transformed into an expanded model of domesticity.